2009
DOI: 10.1080/00291950903368334
|View full text |Cite
|
Sign up to set email alerts
|

Aldo Leopold and stewardship: Lessons for forest planning and management in the Nordic countries?

Abstract: There is a major trend in forest management that local managers are being replaced by entrepreneurs, who are often less placedependent. Entrepreneurs are also more updated when it comes to scientific knowledge and national and international trends in forest values and functions, as well as knowledge about general planning and management concepts that have high value for tourism and recreation. Parallel with the observed changing management culture, there also seems to be an increased abstraction of forest valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…In a previous study [27], we observed how such values tend to be perceived collectively and are shared among different local actors. These shared values tend to facilitate mutual understanding and cooperation, becoming especially relevant for landscape stewardship, as it greatly relies on collaboration and communication within a local community for land management activities [59]. Yet, values that are perceived more individually, such as appreciation of a landscape's existence or gaining personal fulfilment from it, also seem to play an important role, as they were strongly associated with higher levels of awareness and responsibility in our study.…”
Section: Perception Of Landscape Values and Its Connection To Place Amentioning
confidence: 66%
“…In a previous study [27], we observed how such values tend to be perceived collectively and are shared among different local actors. These shared values tend to facilitate mutual understanding and cooperation, becoming especially relevant for landscape stewardship, as it greatly relies on collaboration and communication within a local community for land management activities [59]. Yet, values that are perceived more individually, such as appreciation of a landscape's existence or gaining personal fulfilment from it, also seem to play an important role, as they were strongly associated with higher levels of awareness and responsibility in our study.…”
Section: Perception Of Landscape Values and Its Connection To Place Amentioning
confidence: 66%
“…As a collective practice, this included behavior such as being, making, using, starting, practicing, regarding, perceiving, defining, discussing, and being involved in a place-all of which are elements of forming social networks in a particular place (Amundsen 2012). Care and stewardship of places includes most of what we do and do not do in places (Gundersen & Mäkinen 2009), and some negative practices associated with neglecting, ignoring, and giving up were mentioned by some interviewers. Many of the participants emphasized the utilitarian values of landscape and that the natural resources should be utilzed to their maximum production level to secure the livelihoods of those living in the community.…”
Section: Cultural Perceptions and Beliefsmentioning
confidence: 95%
“…To date, the local flood mitigation measures have been short-term coping strategies rather than long-term adaptation. Sense of place is part of long-standing coping traditions through shared concepts of local identity and well-being being contingent upon landscapes that are familiar and providers of economic income and good livelihoods (Gundersen & Mäkinen 2009;Murphy et al 2015). Among the most prominent place connections for the inhabitants of Gausdal Municipality are the longstanding bonds with each farm and a former way of life that is rarely found today.…”
Section: Constraints To Adapting To Climate Changementioning
confidence: 99%
“…The literature on feelings attached to places does not focus much on specific attributes in landscapes as such. From a management point of view, this approach implies more focus on specific localities and viewing each place as a totality, not just as a sum of attributes that may be manipulated (Gundersen & Mäkinen 2009). …”
Section: Place-based Approaches and Constitutive Valuesmentioning
confidence: 99%